2015
DOI: 10.5380/rber.v4i3.42028
|View full text |Cite
|
Sign up to set email alerts
|

Influência Da Aplicação De Água Resíduaria De Suinocultura No Volume E Índice De Acidez Do Óleo De Soja

Abstract: Com crescimento populacional acelerado, se surge uma demanda alimentícia crescente para o mundo. Produção essa, por sua vez, de responsabilidade do agronegócio. Consequentemente, os sistemas agropecuários de produção de alimentos originam vários tipos de resíduos orgânicos, apresentando alto poder poluente, especialmente para os recursos hídricos, devido a sua elevada Demanda Química de Oxigênio (DQO). Esses resíduos quando manejados e utilizados adequadamente, revertem-se em fornecedores nutricionais, os quai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Batista et al (2019) showed that 1 mg KOH g −1 demonstrates an oil suitable for biofuel production by basic catalysis reactions. De‐Oliveira et al (2015) showed acidity indices from 0.3% to 0.7% for crude soybean oil, with the minimum index indicated by the authors below the maximum stipulated by the national petroleum agency—ANP, however, the maximum index was above such maximum. The acidity indices of safflower oil observed herein were still lower than those observed for Jatropha with 4.82 mg KOH g −1 oil(Bento et al, 2017), Moringa oleifera with 8.85 mg KOH g −1 oil and castor beans with 0.91 mg KOH g −1 oil (Pereira et al, 2016; Pradhan et al, 2012).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Batista et al (2019) showed that 1 mg KOH g −1 demonstrates an oil suitable for biofuel production by basic catalysis reactions. De‐Oliveira et al (2015) showed acidity indices from 0.3% to 0.7% for crude soybean oil, with the minimum index indicated by the authors below the maximum stipulated by the national petroleum agency—ANP, however, the maximum index was above such maximum. The acidity indices of safflower oil observed herein were still lower than those observed for Jatropha with 4.82 mg KOH g −1 oil(Bento et al, 2017), Moringa oleifera with 8.85 mg KOH g −1 oil and castor beans with 0.91 mg KOH g −1 oil (Pereira et al, 2016; Pradhan et al, 2012).…”
Section: Resultsmentioning
confidence: 95%
“…However, high AI indicates that the degree of oil degradation (Greggio and Bonini, 2014) would be related to the formation of soap and decrease in the yield of oil conversion reactions into biodiesel (Giacomin et al, 2017). De‐Oliveira et al (2015) highlights that biodiesel has a chemical nature of acidity parameters that are associated with the chemical nature of the vegetable oil it originated from.…”
Section: Resultsmentioning
confidence: 99%